Obstacle Circumvention and Motor Daily Dual Task During a Simulation of Street Crossing by Individuals with Parkinson’s Disease - Carolina Favarin Soares; Aline Prieto Silveira-Ciola; Lucas Simieli; Patrícia de Aguiar Yamada; Fábio Augusto Barbieri; Flávia Roberta Faganello-Navega (Life)
Parkinson’s disease (PD) causes attentional deficits and worse dual-task (DT) performance, which increases the risk of being run over. In addition to motor deficits, the decision-making ability and the response to external stimuli are impaired. The aim of this study was to evaluate the spatiotemporal parameters of gait during everyday tasks of individuals with PD, specifically during street crossing simulation, obstacle circumvention, and motor DT. People with PD (PG) and matched controls (CG) were distributed into two groups and were evaluated under six different gait and randomized conditions: without a concomitant task (NW); with obstacle circumvention (OC); and four other conditions under simulation of street crossing (without concomitant task (SC); with obstacle circumvention (SCOC); carrying bags (SCB); and carrying bags concomitant to obstacle circumvention (SCOC+B)). The CG group had greater values for all parameters compared to PG, except for double support time. This study’s results found that individuals with PD took smaller, narrower, slower, and shorter steps when compared to neurologically healthy older people and that there was a change in the spatiotemporal gait parameters of all individuals, except for the step-duration parameter under the most difficult crossing conditions.